HISTOMORPHOLOGICAL SPECTRUM OF LIVER AND KIDNEY LESIONS IN AUTOPSY CASES - KUMAR, MOHIT; KP, ATHIRA; BE, CHAITRA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The main objective of this study was to analyze the findings by the histomorphological spectrum of liver and kidney lesions in autopsies. Histopathological evaluation of autopsy specimens helps to identify organ pathologies and determine the cause of death. Methods: The study was carried out among 230 autopsy cases. All the specimens were fixed in 10% formalin, weight and dimensions were recorded. After tissue processing, paraffin blocks sections were studied from liver and kidney specimens. The histological sections were prepared using H and E Stain and microscopic examination was done. Findings were recorded and statistical analysis was performed. Results: Out of the 230 cases evaluated in the present study, 168 liver specimens and 127 kidney specimens were evaluated. Specimens from males were more common compared to females. Age group of 41–60 was found to be most common. Fatty changes in liver and vascular lesions in kidney were most common lesions found in this study. Incidental findings like granuloma and metastatic tumor deposits were found in liver. Incidental finding of simple renal cyst was found in a case of renal autopsy. Conclusion: The present study shows that most common findings are vascular lesions and fatty change in kidney and liver, respectively. Rare lesions like tumor metastasis are also noted. Granulomatous inflammation and simple renal cyst like incidental findings also noted.